2015
DOI: 10.1002/hed.23963
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for late dysphagia after (chemo)radiotherapy for head and neck cancer: A systematic methodological review

Abstract: Although there is no conclusive evidence for dysphagia in patients with head and neck cancer after (chemo)radiotherapy, these data provide evidence to guide clinicians in patients who will have late dysphagia and to choose an optimal prophylactic strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 65 publications
(75 reference statements)
0
24
0
5
Order By: Relevance
“…Threepoint ordinal scales (range 0-2) were used to capture pooling severity. The categorical rating scale comprises three levels of pooling severity: no pooling (0), mild-to-moderate pooling (1), and severe pooling (2). The description of each ordinal level of the severity of pooling is based on the perceptual judgment of the amount of bolus in relation to the size of the valleculae and/or pyriform sinuses.…”
Section: Fees Outcome Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Threepoint ordinal scales (range 0-2) were used to capture pooling severity. The categorical rating scale comprises three levels of pooling severity: no pooling (0), mild-to-moderate pooling (1), and severe pooling (2). The description of each ordinal level of the severity of pooling is based on the perceptual judgment of the amount of bolus in relation to the size of the valleculae and/or pyriform sinuses.…”
Section: Fees Outcome Variablesmentioning
confidence: 99%
“…Treatment-induced alterations that contribute to OD include xerostomia, lymphedema, fibrosis, and damage to neuromuscular structures. Furthermore, chemoradiotherapy and the presence of hypopharyngeal carcinoma are associated with an increased risk for late OD [2]. Common symptoms of swallowing impairment in HNC patients while eating include complaints of food 'sticking' in the throat, nasal regurgitation, coughing, or choking [3].…”
Section: Introductionmentioning
confidence: 99%
“…19 Jiang et al have demonstrated that a hypopharyngeal tumor site and the existence of pretreatment dysphagia, are factors of late dysphagia worsening. 31 Moreover, Gluck et al has stressed the importance of considering the toxicities of lower grade (NCI-CTCAE Grades 1 and 2) to have an adequate estimation of the dysphagia burden. 15 In previous papers, the estimated prevalence of dysphagia during and after chemoradiotherapy/radiotherapy varies from 43% to 64% by instrumental measure.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have associated more advanced tumor classification with worse swallowing scores and higher rates of gastrostomy tube placement . Radiation therapy and combined chemoradiation have been associated with higher rates of dysphagia, stricture, pneumonia, and prolonged gastrostomy tube dependence, along with a lower likelihood of eating a normal diet . Poor swallowing function prior to HNC has been associated with worse swallowing function after treatment .…”
Section: Introductionmentioning
confidence: 99%